PENERAPAN PHOTOGRAMMETRY BERBASIS SMARTPHONE DALAM PERANCANGAN AR BOOK PANDUAN SENI RUPA UNTUK ANAK SEKOLAH DASAR - Muhammad Nabil Oktanuryansyah; Ester Anggun Kusumaningtyas (Universitas Budi Luhur, 2024)
Photogrammetry is a technique or process for measuring, mapping, and creating a three-dimensional model of a physical object by combining overlapping image data. With advancements in technology, photogrammetry can be achieved by relying on smartphone camera technology. This application can be implemented into an interactive medium, one of which is an augmented reality book introducing art to children. This can be accomplished because the fundamental concept of augmented reality involves merging physical objects, virtual objects, and detailed information seamlessly, providing detailed and scientific visualization. Therefore, the design of an AR book modeling is required, implementing smartphone-based photogrammetry techniques using the single-lens close-range photogrammetry method. This ensures the effective and flexible utilization of such techniques in the creative industry. Heuristic evaluation testing is conducted to assess the quality of the developed media.